The Spectrum of Severity: Clinical and Hematological Markers in Jakarta’s COVID-19 Patients - Erlin Listiyaningsih; Shinta Dewi Permata Sari; Dewi Martalena; Wawang Sukarya (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Jakarta, a densely populated megacity with high hybrid immunity, presents a unique epidemiological landscape for COVID-19. Understanding the clinical and hematological markers in this context is vital for improving clinical management. This study aims to analyze the clinical and hematological profiles of COVID-19 patients in Jakarta to identify markers associated with disease severity. This cross-sectional study analyzed secondary data from 100 confirmed COVID-19 patients (26 mild, 54 moderate, 20 severe) at two Jakarta hospitals. ANOVA and Kruskal-Wallis tests were employed to compare variables across severity groups, while categorical variables were analyzed using Chi-square tests. Significant associations with increasing severity were found for higher HR and RR. Among hematological parameters, basophil levels decreased significantly with higher severity. Although not statistically significant, trends of decreasing lymphocytes and platelets, alongside increasing blood glucose and neutrophils, were observed. Diabetes was the most prevalent comorbidity in severe cases. In conclusion, HR, RR, and basophils roles as significant markers of COVID-19 severity in our population. Trends in lymphocyte, thrombocyte, blood glucose, and diabetes prevalence, align with known patterns of severe disease with insignificant statistically, due to sample size limitations.